Earl interrupted - Forester, Amanda (Forester, Amanda. Daring marriages., 2018)
"Captain Robert Ashton, Earl of Darington, knows finding a bride in London will not be easy―not since he has been notoriously dubbed as the "Pirate Earl". What he didn't expect was to get abducted-and to have his escape go horribly awry when an innocent lady gets caught in the crossfire. Amateur physician Emma St. James is on her way to meet her betrothed when she is rescued by an injured gentleman. Despite her shock after discovering he is the Pirate Earl, Emma feels drawn to the man who saved her life. Duty forces them apart, but when they meet again on the high seas, Darington will risk all-his fortune, his name, and even his life to keep her safe."